Optimised Flywheel-Assisted Regenerative Braking for Enhanced Energy Recovery and Voltage Stability in Electric Vehicles - Masri, Jafar; Ismail, Mohammad (Automotive Laboratory of Universitas Muhammadiyah Magelang in collaboration with Association of Indonesian Vocational Educators (AIVE), 2025)
This study presents a flywheel-assisted regenerative braking system (FARBS) designed to improve energy recovery and voltage stability in electric vehicles (EVs). Conventional regenerative braking systems (RBS) suffer from short energy retention durations and voltage fluctuations, limiting their efficiency. The proposed system incorporates a spherical shell flywheel (120 mm radius, 20 mm thickness, 3 kg mass) directly into the braking mechanism to prolong energy recovery and optimise braking efficiency. Experimental results demonstrate a 439% increase in energy recovery duration, extending from 1.15 seconds (2000 RPM) to 6.2 seconds (4500 RPM). Voltage retention improves significantly, increasing from 10.3V to 19.2V, ensuring sustained voltage delivery. Kinetic energy storage attains 580 J at 4500 RPM, exhibiting a 23.4% increase over 2000 RPM. The flywheel system quadruples power output longevity, sustaining 6.40 W for 6.2 seconds at 4500 RPM, compared to 2.2 seconds without the flywheel. Energy recovery efficiency peaks at 16 J at 4500 RPM, an improvement of 275% in comparison to the baseline 4 J. Optimisation analysis confirms that increasing flywheel mass (1 kg to 3 kg) improves energy recovery by 194%, while a spherical shell flywheel improves energy recovery, achieving 327 J. This is twice as much as that of a solid disk (162 J). Carbon fibre outperforms steel, boosting energy recovery by 94%, while increasing the thickness from 10 mm to 20 mm, and resulting in a 200% efficiency gain. These findings underline the superiority of flywheel-assisted energy recovery, paving the way for high-efficiency braking solutions in EVs, public transportation and railway networks.